The Effect of Perceived Risk and Service Quality on Revisit Intention on Bukik Gadang Hot Springs Tourism Object at Nagari Koto Gadang Koto Anau with Destination Image as a Mediation Variable - Yasri; Moudiana Faren (Marketing Management Studies, 2021)
The purpose of this study was to analyze: (1) The Effect of Perceived Risk on Destination Image on Bukik Gadang Hot Springs Tourism Object, (2) The Effect of Service Quality on Destination Image on Bukik Gadang Hot Springs Tourism Object, (3) The Effect of Destination Image on Revisit Intention on Bukik Gadang Hot Springs Tourism Object, (4) The Effect of Perceived Risk on Revisit Intentions on Bukik Gadang Hot Springs Tourism Objects, (5) The Effect of Service Quality to Revisit Intentions on Bukik Gadang Hot Springs Tourism Objects, (6) The Mediation Role of Destination Image between Perceived Risk and Revisit Intention, (7) The Mediation Role of Destination Image between Service Quality and Revisit. This research is classified as explonatory research. The population of this research is people who have visited the Bukik Gadang hot spring tourism object using purposive sampling method. The number of samples in this study were 151 samples. The data used are primary and secondary data obtained through distributing questionnaires to tourists. The analytical method used is descriptive analysis and quantitative analysis using Structural Equation Model (SEM) with Partial Least Square (PLS) approach. The results in this study: (1) Perceived Risk has a significant effect on Destination Image at Bukik Gadang Hot Springs Tourism Object, (2) Service Quality has a significant effect on Destination Image on Bukik Gadang Hot Springs Tourism Object, (3) Destination Image has a significant effect on the Revisit Intention of the Bukik Gadang Hot Springs Tourism Object, (4) Perceived Risk has a significant effect on the Revisit Intention of the Bukik Gadang Hot Springs Tourism Object, (5) Service Quality has a significant effect on the Revisit Intention of the Bukik Gadang Hot Springs Tourism Object, (6) Destination Image significantly mediates the relationship between Perceived Risk and Revisit Intention, (7) Destination Image significantly mediates the relationship between Perceived Risk and Revisit Intention.